POLITIK HUKUM KEDUDUKAN PERATURAN DESA DALAM HIERARKI PERATURAN PERUNDANG-UNDANGAN BERDASARKAN UNDANG- UNDANG NO 12 TAHUN 2011 TENTANG PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN - Muhammad Armada. S; Mexsasai Indra; Gusliana HB (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The village is an important part of the Indonesian constitution. When viewed from thenature of the Indonesian state which contains the ideals of the state regarding the justification of theIndonesian state, regarding the formation of the Indonesian state, as well as regarding the objectivesof the Indonesian state, basically all of these are the same as the essence, justification of existence,formation and purpose of the village. Attamimi said that all of this was of course in a much largerscope and in a more modern context in accordance with the era and period when the Republic ofIndonesia was proclaimed. Soepomo even said that the ideals of the country are basically containedin the village community association which consists of its leaders and the people. Soepomo alsoemphasized that the state model known as the Village Republic is the original model of Indonesiangovernment, this is because the basic ideals of forming a Republic of Indonesia government are thesame as the ideals of forming a Village Republic, which is adapted to the real social structure ofIndonesian society. In fact, the form of village government existed long before there wascolonialism by the Dutch East Indies government, as emphasized by Van Vollenhoven.The research method used in this thesis is normative research using a statutory approach.The main data in this study is secondary data, namely legal literature which consists of severalquotations from various related literature sources. The other supporting research data used byresearchers are primary legal materials, secondary legal materials and tertiary legal materials.From the discussion and research conducted by the researcher, there are several conclusionsthat can be obtained. First, basically, the position status of village regulations in the hierarchy oflaws and regulations in Indonesia is Wettelijk Regeling, which is a type of law. This confirms thatvillage regulations are legal products in the form of laws which basically must be regulated andconfirmed in the hierarchy of laws and regulations in Indonesia. Second, that it is necessary toinclude village regulations in the hierarchy of laws and regulations in Indonesia to emphasize theposition and legal certainty of village regulations.Keywords : Legal Politics - Village Regulations - Laws